Aerobic biological treatment by fluidized bed : an experimental approach - Illangovan, Patchamuthu; Nguyen, Cong Thanh; Vigneswaran, Saravanamuthu; Samorn Muttamara; Norwegian Agency for Development (NORAD) (Bangkok : Asian Institute of Technology, 1985)
An aerobic tapered fluidized bed reactor was measured in terms of organic removal efficiency and dissolved oxygen concentration maintained in the reactor. The uniqueness about this process is the combined activity of suspended and attached growth microorganisms in organic removal. Attached growth microorganism were predominant in the fludized sand media while suspended growth microorganisms were dominant in the portion above the expanded bed in the reactor. The study show moderate organic carbon removal efficiency (45-50%) at low concentration dissolved oxygen 9.9-10.2 mg/l and low detention time of 1.8-2.3 min. It can be deduced from the study that the organic carbon removal efficiency is dependent upon the influent dissolved oxygen concentration.
A thesis submitted in partial fulfillment of requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Sewage -- Purification -- Biological treatment; Fluidized reactors